2019
DOI: 10.1371/journal.pone.0219500
|View full text |Cite
|
Sign up to set email alerts
|

Economic evaluation of a childhood obesity prevention programme for children: Results from the WAVES cluster randomised controlled trial conducted in schools

Abstract: Background Childhood obesity is a serious public health challenge and schools have been identified as an ideal place to implement prevention interventions. The aim of this study was to measure the cost-effectiveness of a multi-faceted school-based obesity prevention intervention targeting children aged 6–7 years when compared to ‘usual activities’. Methods A cluster randomised controlled trial in 54 schools across the West Midlands (UK) was conducted. The 12-month inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 24 publications
0
24
1
Order By: Relevance
“…The economic evaluation of the Healthy Caregivers-Healthy Children (HC2) program, which is an early childcare center-based obesity prevention program, suggested that the HC2 intervention shows potential for generating cost savings [42]. One study (the WAVES study) [43] assessing the cost-effectiveness of a multi-faceted school-based obesity prevention intervention targeting children aged 6-7 years suggested that more research to explore obesity prevention within schools as part of a wider systems approach to obesity prevention are needed. One study also assessed the cost-effectiveness of a large, multifaceted, community-based capacity-building demonstration program (Be Active Eat Well (BAEW)) and suggested that BAEW was affordable and cost-effective [44].…”
Section: Secondary Outcomesmentioning
confidence: 99%
“…The economic evaluation of the Healthy Caregivers-Healthy Children (HC2) program, which is an early childcare center-based obesity prevention program, suggested that the HC2 intervention shows potential for generating cost savings [42]. One study (the WAVES study) [43] assessing the cost-effectiveness of a multi-faceted school-based obesity prevention intervention targeting children aged 6-7 years suggested that more research to explore obesity prevention within schools as part of a wider systems approach to obesity prevention are needed. One study also assessed the cost-effectiveness of a large, multifaceted, community-based capacity-building demonstration program (Be Active Eat Well (BAEW)) and suggested that BAEW was affordable and cost-effective [44].…”
Section: Secondary Outcomesmentioning
confidence: 99%
“…We are unaware of other obesity prevention interventions delivered in infancy that have reported cost‐utility ICERs; however, a school‐based physical activity intervention for primary‐aged children in the UK reported an ICER of £26,815 (A$54,894, US$38,307) per QALY (43), indicating poorer cost‐utility than the Sleep intervention and better cost‐utility than the Combination intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Speci cally, there are no comparable economic evaluations of implementation-interventions in this setting focussed on childhood obesity. More broadly, there are published economic evaluations of early childhood obesity prevention interventions conducted in other countries (49)(50)(51) and these studies are typically inconclusive in their assessment of cost-effectiveness given uncertainty in measures of effect.…”
Section: Discussionmentioning
confidence: 99%